Use of plant viruses and virus-like particles for the creation of novel vaccines - Balke, Ina; Zeltins, Andris (Advanced drug delivery reviews, 2019)
In recent decades, the development of plant virology and genetic engineering techniques has resulted in the construction of plant virus-based vaccines for protection against different infectious agents, cancers and autoimmune diseases in both humans and animals. Interaction studies between plant viruses and mammalian organisms have suggested that plant viruses and virus-like particles (VLPs) are safe and noninfectious to humans and animals. Plant viruses with introduced antigens are powerful vaccine components due to their strongly organized, repetitive spatial structure; they can elicit strong immune responses similar to those observed with infectious mammalian viruses. The analysis of published data demonstrated that at least 73 experimental vaccines, including 61 prophylactic and 12 therapeutic vaccines, have been constructed using plant viruses as a carrier structure for presentation of different antigens. This information clearly demonstrates that noninfectious viruses are also applicable as vaccine carriers. Moreover, several plant viruses have been used for platform development, and corresponding vaccines are currently being tested in human and veterinary clinical trials. This review therefore discusses the main principles of plant VLP vaccine construction, emphasizing the physical, chemical, genetic and immunological aspects. Results of the latest studies suggest that several plant virus-based vaccines will join the list of approved human and animal vaccines in the near future. [Display omitted]